(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Maternal anemia remains one of the most common nutritional disorders during pregnancy and is associated with adverse maternal and neonatal outcomes. Reduced maternal Hb (Haemoglobin) levels may impair fetal oxygenation and growth, leading to alterations in neonatal anthropometric parameters. This study was conducted to evaluate the relationship between maternal haemoglobin, umbilical cord haemoglobin, and neonatal anthropometric measurements in term newborns. Methods: A descriptive cross-sectional study was conducted over one year (February 2024–January 2025) at ACSR Government Medical College and Hospital, Nellore. A total of 404 healthy term neonates and their mothers meeting the inclusion criteria were enrolled. Maternal pre-delivery haemoglobin and umbilical cord haemoglobin were estimated using an automated hematology analyzer. Mothers were classified according to WHO criteria into mild and moderate anemia groups. Neonatal anthropometric parameters including birth weight, length, and head circumference were recorded. Statistical analysis was performed using SPSS version 26. A student’s t-test and Pearson’s correlation coefficient were used, with p<0.05 considered statistically significant. Results: The mean maternal haemoglobin was 9.16 ± 0.94 g/dL, while the mean cord haemoglobin was 11.49 ± 1.08 g/dL. Among the mothers, 76% had moderate anemia and 24% had mild anemia. Low birth weight was observed in 18.5% of newborns. Maternal and cord haemoglobin levels were significantly lower in the moderate anemia group compared with the mild anemia group (p<0.01). A significant positive correlation was found between maternal and cord haemoglobin levels (r=0.598, p=0.001). However, maternal haemoglobin showed no statistically significant correlation with neonatal birth weight, length, or head circumference. Conclusion: Maternal hemoglobin has a significant positive influence on neonatal cord haemoglobin, emphasizing the close hematological relationship between mother and fetus. Although maternal anemia did not significantly affect neonatal anthropometric measurements in this study, improving maternal hemoglobin status during pregnancy remains essential to optimize neonatal health and prevent adverse outcomes.